Fabrication of branch-like Aph@LDH-MgO material through organic-inorganic hybrid conjugation for excellent anti-corrosion performance - Maryam Chafiq; Abdelkarim Chaouiki; Rachid Salghi; Young Gun Ko (Journal of Magnesium and Alloys, 2023)
Layered double hydroxides (LDH) frameworks have shown significant enhancement in stability and reusability, and their tailorable architecture brings new insight into the development of the next generation of hybrid materials, which attracted considerable attention in many fields over the years. One of the factors contributing to the widespread applicability of layered double hydroxides is their adaptable composition, which can accommodate a wide spectrum of potential anionic guests. This exceptional property makes the LDH system simple to adjust for various applications. However, most LDH systems are synthesized in situ in an autoclave at high temperatures and pressures that severely restrict the industrial use of such coating systems. In this study, LDH was directly synthesized on a magnesium alloy that had undergone plasma electrolytic oxidation (PEO) treatment in the presence of ethylenediaminetetraacetic acid, thereby avoiding the use of hydrothermal autoclave conditions. This LDH system was compared with a hybrid architecture consisting of organic-inorganic self-assembly. An organic layer was fabricated on top of the LDH film using 4-Aminophenol (Aph) compound, resulting in a smart hierarchical structure that can provide a robust Aph@LDH film with excellent anti-corrosion performance. At the molecular level, the conjugation characteristics and adsorption mechanism of Aph molecule were studied using two levels of theory as follows. First, Localized orbit locator (LOL)-π isosurface, electrostatic potential (ESP) distribution, and average local ionization energy (ALIE) on the molecular surface were used to highlight localization region, reveal the favorable electrophilic and nucleophilic attacks, and clearly explore the type of interactions that occurred around interesting regions. Second, first-principles based on density functional theory (DFT) was applied to study the hybrid mechanism of Aph on LDH system and elucidate their mutual interactions. The experimental and computational analyses suggest that the high π-electron density and delocalization characteristics of the functional groups and benzene ring in the Aph molecule played a leading role in the synergistic effects arising from the combination of organic and inorganic coatings. This work provides a promising approach to design advanced hybrid materials with exceptional electrochemical performance.